STUDY PLASMA SODIUM DISTURBANCES ON SEVERE TRAUMATIC BRAIN INJURY PATIENTS (Vietnam Journal of Community Medicine, 2022)
Introduction: Traumatic brain injury (TBI) is a common emergency in . The severity of TBI isdetermined by the damage as primary or secondary. Secondary injury might change TBI patientsfrom mild to severe and might become the main cause of death in these ones. Hypernatremia hasbeen considered as one of the main causes of secondary injury in TBI patients.Objective: To detect changes of sodium levels in blood of pediatric patients who has TBI andsome factors related to these disorders.Subjects and methods: A cross-sectional descriptive study, 88 patients in the group of2months - 15years old. Results: The average rate of dysnatremia was 35%. Hyponatremiarepresented 26%, hypernatremia represented 9%. Hypernatremia increases the number of days onmechanical ventilation. Hypernatremia has a higher rate in the group of patients with severe TBI(Glasgow ≤ 8 points) and complex injury on computed tomography (CT) of the brain.Conclusions: Hyponatremia is more common than hypernatremia. However, the prevalence ofhypernatremia is higher in patients with severe TBI. In general, hyponatremia increases theduration of mechanical ventilation, so it should be diagnosed and treated at the earliest.
Keywords: Traumatic brain injury, pediatric patient, blood sodium level, hypernatremia, hyponatremia.